Human motion detection and classification - Khalifa, Othman Omran; Awang, Mat Kamil; Hassan Abdalla Hashim, Aisha (IIUM Press, 2011)
Human Motion Detection is one of the most challenging problems in computer vision due to the huge quantity of possible cases. The number of postures depends on the degree of freedom of the human body (i.e. the articulations such as shoulders or knees). Moreover, the morphology of the person (height, corpulence, etc) influences the perception of the posture.vFurthermore, clothes can also give different types of appearances for the same posture